2018
DOI: 10.1177/0003319718767737
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of Percutaneously Completed Coronary Revascularization in Stable Coronary Artery Disease: Obstructive Versus Occlusive Lesions

Abstract: Our study sought to assess long-term outcomes of percutaneously completed coronary revascularization (CCR) in patients with obstructive coronary artery disease (CAD) comprising chronic total occlusions (CTOs). Between 2010 and 2014, percutaneous coronary interventions (PCIs) of the CTOs were attempted in 213 patients: the CCR was achieved in 125 patients (group 1), while the PCI failed in 88 patients (group 2). They were matched against 252 patients (group 3) with the CCR obtained by the non-CTO PCIs. In the 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…8 In a previous issue of Angiology, we presented our experience with stable patients in whom a complete coronary revascularization (CCR) was percutaneously achieved. 9 Our study was a single-center registry analysis with related pitfalls and, as such, adequately mirrored the real-world situation. We enrolled 465 patients assigned into 3 groups (group 1: successful CTO PCI, group 2: failed CTO PCI, and group 3: successful non-CTO PCI).…”
mentioning
confidence: 78%
“…8 In a previous issue of Angiology, we presented our experience with stable patients in whom a complete coronary revascularization (CCR) was percutaneously achieved. 9 Our study was a single-center registry analysis with related pitfalls and, as such, adequately mirrored the real-world situation. We enrolled 465 patients assigned into 3 groups (group 1: successful CTO PCI, group 2: failed CTO PCI, and group 3: successful non-CTO PCI).…”
mentioning
confidence: 78%
“…There is an ongoing discussion concerning the possibility of using CFR in patients with chronic angina who are candidates for percutaneous revascularization of CTOs. There are data from our CTO registry confirming the clinical efficacy of successful PCI of LAD, RCA, LCX in reducing RA in 6-year follow-up (55%, 35%, less than 5%, respectively) [23]. However, in the light of the recent CTO studies' conflicting results, there is still a debate regarding the clinical efficacy of CTO interventions at improving angina frequency, physical limitation and quality of life [24] [25].…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Additionally, in the absence of a large burden of ischemia or viable myocardium, there is lack of evidence regarding prognostic benefit of CTO PCI. 7 Therefore, in the study by Kranjec et al, 3 arbitrary patient selection and failed CTO PCI-related adverse events may have an effect on higher frequency of MACE, irrespective of revascularization.…”
mentioning
confidence: 98%
“…1,2 PCI may provide prognostic benefit in accurately selected patients with CTO; however, routine treatment with PCI may not be useful and may even be harmful in most cases. 2 Recently, Kranjec et al 3 concluded that performing a successful CTO PCI may be associated with similar clinical outcomes in patients with single-vessel non-CTO successful PCI and provides better long-term clinical outcomes compared with patients in whom CTO PCI failed. On the other hand, patients undergoing CTO PCI carry a risk of hazardous complications that may affect prognosis, irrespective of procedure success.…”
mentioning
confidence: 99%
See 1 more Smart Citation